Fossils of governance - Prasad, A. (Delhi, 2007)
The book presents an interesting and absorbing study of the issues of governance, ethics, character, morality and the mindset. It takes the readers through the author's long years of experience in the different Ministries of the Government of India
Keywords: Bureaucrats-Journey